2010
DOI: 10.1259/dmfr/80778956
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic evaluation of mouth breathers among paediatric patients

Abstract: It is clear that adenoids have a dominant role in causing mouth breathing. Yet, we recommend that paediatricians should assess other mechanical obstacles if mouth breathing was not corrected after adenoidectomy. Further research should be performed to test the validity of correction of such factors in improving the quality of life of mouth-breathing children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 27 publications
2
48
0
1
Order By: Relevance
“…Another finding in our study was inadequate resting lip posture, with most children showing a lips-apart posture, which corroborates other studies 3,10,15,20,23 . However, changes in cheek tension and resting tongue posture, mentioned in the literature 20 , were not identified in our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another finding in our study was inadequate resting lip posture, with most children showing a lips-apart posture, which corroborates other studies 3,10,15,20,23 . However, changes in cheek tension and resting tongue posture, mentioned in the literature 20 , were not identified in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown a variety of causes for mouth breathing 5,7,10,11 . The children whose charts were reviewed in the present study had rhinitis and a positive skin test, as well as nasal mucosa abnormalities and hypertrophic tonsils and adenoids.…”
Section: Discussionmentioning
confidence: 99%
“…3e5 As mouth becomes the primary means of breathing, there is a reduced or complete loss of function of nose, which shows underdevelopment or stunted growth (change in form). 6,7 According to Moss 6 "All growth changes in size, shape, and spatial position, and the maintenance of all skeletal units are always secondary to specific functional matrices." (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Much attention has been paid to the relationship between respiratory function and facial morphology. 7 Some articles have analysed the dimensions of the upper airway in patients with different sagittal and vertical skeletal facial morphologies using lateral cephalograms. 5,6,8 Class II patients have a narrower anteroposterior pharyngeal dimension, and this narrowing is specifically noted in the nasopharynx area at the hard palate level and in the oropharynx at the level of the tip of the soft palate and the mandible.…”
mentioning
confidence: 99%